Novel AZSPWM Algorithms based VCIMD for Reduced CMV Variations - J. Amarnath; A. Kailasa Rao; K. Satyanarayana (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
Novel AZSPWM algorithms based on the concept of imaginary switching times (IST) are presented in this paper for vector controlled induction motor drive to reduce the common mode voltage (CMV) variations. The proposed algorithms did not use the information of angle and sector and hence reduces the complexity involved in the conventional space vector PWM (CSVPWM) approach. The proposed AZSPWM algorithms did not use zero voltage vectors and involves utilizing the two adjacent voltage vectors along with two opposing active voltage vectors with equal duty cycle to provide cancellation and create an effective zero state. Moreover, these algorithms are developed based on the concept of imaginary switching times, the computational burden involved in the conventional algorithms can be decreased. To verify these algorithms, numerical simulation studies have been carried out and results are presented and compared with the CSVPWM algorithm.DOI: http://dx.doi.org/10.11591/ijpeds.v3i1.1337